Consanguineous marriages, premarital screening, and genetic testing: a survey among Saudi university students - Jameel, Tahir; Baig, Mukhtiar; Murad, Manal Abdulaziz; Gazzaz, Zohair Jamil; Mal, Youssof; Alyoubi, Wedyan Eid; Alyoubi, Ghadi Hamed; Alaslani, Shoug Tawfiq; Alshuaibi, Hanan Abdullah; Nawaz, Ayesha; Alkaabi, Turki (Frontiers in Public Health, 2024)
Background Marriage among cousins or close relatives, i.e., consanguinity, is prevalent in many parts of the world, especially the Muslim world. Across civilizations, cultural norms, religious beliefs, and economic factors affect consanguineous marriages (CMs); however, such marriages have social, genetic, and health repercussions. The present study investigated the university students’ attitudes regarding CMs and factors influencing their attitudes at King Abdulaziz University (KAU), Jeddah, Kingdom of Saudi Arabia (KSA). Methods This cross-sectional prospective study was conducted at KAU Jeddah in 2023. The questionnaire was distributed via electronic media (Emails, Facebook Messenger & WhatsApp). The convenience sampling technique was used to select participants, and descriptive and inferential statistics were used to analyze the data on SPSS-26. Results A total of 1707 university students were part of the study (females, 1,198, 70.2%; males, 509, 29.8%). Almost half of the participants, 819 (48.0%), had parents with CMs. Most of the participants, 1,391 (81.5%), had CMs in the family. Half of the participants disagreed that parents consider marriage stable due to high compatibility and the same social relationship before and after marriage. About one-third of respondents said parents believe family marriage transmits cultural values and continuity and keeps wealth in the family. More than three-fourths of the participants stated that if marriage is arranged with first cousins, they will opt for genetic analysis (82.5%) and premarital counseling (85.2%). The personal attitudes of females (p < 0.001), undergraduate (p = 0.02), and health sciences students (p = 0.02) were more positive than their counterparts. Males (OR = 0.41; p < 0.001) and non-health sciences students (OR = 0.68; p = 0.01) were less likely to have significant positive attitudes than their counterparts. Among participants who had CM parents, males (OR = 0.397; p < 0.001) and non-health sciences students (OR = 0.60; p = 0.01) and urban residents (OR = 0.59; p = 0.01) had significantly lower odds of having a positive attitude than their counterparts. Conclusion The practice of CMs is still prevalent in Saudi culture, with almost half of the participants having CM parents and the majority reporting these marriages in their families. Personal attitudes toward CMs were extremely positive. Most students prefer genetic testing and premarital counseling if marrying first cousins. Gender, faculty, parental income, and educational background influenced participants’ attitudes.